THE EFFECT OF ACIDITY LEVEL AND SUBMERSION DURATION OF TEETH IN PEATLANDS TO DETERMINE BLOOD-GROUP ACCURACY THROUGH DENTAL PULP Study of postmortem blood-group identification technique through dental pulp - DH, Irnamanda; Aflanie, Iwan; Raban, Meka Aulia; Habibah, Ainul (FKG Unlam, 2017)
Background: Indonesia has peatlands which spread all over the state and one of them is in Borneo(Kalimantan). More than three million hectares of peatland spreads in South Borneo. Peatlands have relativelyhigh acidity level with pH range of 3-5. The peatlands in South Borneo is generally used for farming or publiccemetery. In certain situation, peatlands is often used as a dumping ground for criminal victims. Sometimes, theauthority finds it hard to identify the victim because the body is already decomposed. To identify the victim andto analyse the cause of death, identification process is necessary. Teeth can be used to help the identificationprocess. Biological elements from the teeth namely dental pulp contains antigens that were useful to bloodgroupsdetermination by absorption elution method. Purpose: The objective of this research is to discover theeffect of peatlands acidity level and teeth submersions durations in determining blood-group accuracy fromdental pulp. Method: The method of this research used a quasi-experimental method to discover the effect ofpeatlands acidity and pre-experimental method to discover the effect of teeth submersions duration. Thisresearch used 48 pieces premolar teeth that were divided into 8 groups, control group, group submerged onpeatlands with pH 3,0-3,9, pH 4,0-4,9 and pH 5,0-5,9 to discover the effect of peatlands acidity and 1-day, 3-day, 5-day and 7-day groups to discover the effect of teeth submersions time. Result: Fishers Exact test resultsshowed p value 0,314 (p > 0,05) for the effect of peatlands acidity and p value 0,410 (p > 0,05) for the effect ofteeth submersions duration. Conclusion: It could be concluded that there are no effect of the peatlands acidityand teeth submersions time to determine blood-group accuracy from dental pulp.